(3EOGQI GdLhOI GdTGedI (BTQM :s (3WQjbc ddMUhd Ydi TgGOI GdBjRh (B/s - (3GdUjQaj, eMeOs ((3GdGScfOQjI(B: s (3eDSSSI MhQS GdOhdjI(B, s, 2006)
(3Gdeaghe GdMOjK ddLhOI,JWhQ eaghe GdLhOI,Gdeaghe GdTGed ddLhOI,eSFhdjI JMOjO GdLhOI,CgOGa GdLhOI,SjGSGJ GdLhOI,OYGFe GdLhOI,bjGS eSJhi GdLhOI,eLGdGJ JWHjb GdLhOI,GdLhOI GdTGedI,JNWjW GdLhOI GdTGedI,fXGe eYdheGJ GdLhOI,GdJZjjQGJ GdJj jJWdHgG JWHjb GdLhOI GdTGedI,feGPL EOGQI GdLhOI GdTGedI,eJi jfLM aj JMbjb GdLhOI GdTGedIs
(3HHdjhZQGajG(B:(3U(B.283-284s
Keywords: (3LhOI GdEfJGLs; (3VHW GdLhOIs